(untitled) (Journal of Plant Disease Sciences, 2026)
Okra (Abelmoschus esculentus L. Moench) is an economically important vegetable crop cultivated widely in tropical and subtropical regions. However, its productivity is adversely affected by several diseases, among which powdery mildew caused by Erysiphe cichoracearum is one of the most destructive, resulting in severe infections on leaves, stems, and pods. The disease reduces photosynthetic activity, suppresses plant growth, and causes significant yield losses under favourable environmental conditions. A field experiment was conducted to evaluate the efficacy of different fungicides and bioagents for the management of powdery mildew in okra. Among the fungicidal treatments, Myclobutanil 10% WP proved to be the most effective, followed by Azoxystrobin 23% SC. Myclobutanil 10% WP recorded the highest disease control (74.33%) over the untreated control, produced the maximum yield of 138.77 q ha⁻¹, and achieved the highest benefit–cost ratio (1:3.73). Among the bioagents, Ampelomyces quisqualis was comparatively more effective, providing 52.87% disease control with a benefit–cost ratio of 1:2.98. The findings indicate that Myclobutanil 10% WP is highly effective for managing powdery mildew of okra, while Ampelomyces quisqualis may serve as a promising eco-friendly component in integrated disease management strategies.